Different outcomes of spontaneous gall bladder perforation owing to timing of surgical intervention: report of 2 cases - Dakhani, Nawaz M.; Lamani, Yamanur P. (International Surgery Journal, 2020)
Gall bladder perforation (GBP) is a rare life-threatening complication with a high mortality due to atypical clinical presentation and delay in diagnosis due to atypical clinical presentation. Case report 1, 70-year-old female presented with complaints of pain abdomen, vomiting and blackish pigmentation over abdomen since a week. She was in shock on presentation, with necrotic patch over abdomen and abscess collection at umbilicus. Ultrasound revealed GBP at fundus with thick collection in gastrohepatic recess with overlying abdominal wall cellulitis. CECT was not possible and the patient could not be taken for surgery due to unstable vitals and expired the next day. Case report 2, a 68-year-old male presented with complaints of pain abdomen over right side with vomiting. Abdomen was tender diffusely with guarding in right hypochondrium. Ultrasound showed distended gall bladder (GB) with multiple calculi. Magnetic resonance cholangiopancreatography (MRCP) showed a GBP at fundus with pericholecystic collection extending into hepatogastric recess. He underwent total cholecystectomy and post-operative period was uneventful. Acute cholecystitis has a perforation rate of 2-11% due to cystic duct obstruction, ischemia and necrosis. Our first patient had type-III GBP and was in shock and did not survive due to bad condition on arrival whereas the second patient had type-I GBP and underwent cholecystectomy without any complications. Type-I and type-II GBP as proposed by Niemeier have better outcomes compared to type-III. Rapid diagnosis and surgical intervention are very much necessary for reducing mortality as they rarely present with typical signs and symptoms of perforation.